A Normative Anatomic Study of the Glenohumeral Joint and Rotator Cuff Tendons. (September 2014) - Manoharan, Vivek; Sheng, Jia-Min; Chou, Siaw Meng; Yew, Andy Khye Soon; Tan, Soon Huat; Lie, Denny Tijauw Tjoen
Introduction: The purpose of this study is to determine normative values relating to the glenohumeral joint and rotator cuff tendons namely length, width, thickness and footprint of supraspinatus (SS), infraspinatus (IS), teres minor ™ and subscapularis (SC) from 19 specimens. Methods: Rotator cuff tendons and humerus dimensions were measured directly using a digital vernier calliper. In addition, moduli values of rotator cuff tendons were obtained from tensile tests on twelve cadaveric shoulders. The tendon footprints were delineated onto a tracing paper and their dimensions were calculated using digitiser software. The glenoid dimensions were obtained from marking its outline onto a tracing paper and the cavity dimensions from wax moulds. The results were tabulated and statistical analyses, including Student's t-test and ANOVA, were performed. Conclusion: The normative anatomic values obtained can be used in finite element modeling, computer simulation, design of implants and surgery.